PB Discussion Club “MY FUTURE HOME” - Gladkova, Ekaterina; Grigoryeva, Elena; Dorofeev, Pavel; Kazakova, Valentina; Lidin, Konstantin; Sokolov, Stanislav; Kholyavko, Anastasia (project baikal, 2023)
A roundtable discussion on the topic “My future home” was held in the editorial office of Project Baikal on February 28, 2023. A number of issues related to the topic of housing were proposed for the discussion: what housing is perceived as the most comfortable, cozy and convenient. Various opinions have been expressed, but the common denominator characterizes optimal housing as a place where you can feel safe and secure in the long term. At the same time, young architects have demonstrated that mobility, the ability to change their place and lifestyle is also of high value to them. In general, it can be said that the most desirable state is a balance between stability and mobility without having to choose either one.